Hyperuricemia as a risk factor for increase severity of coronary vessel occlusion disease: a cross-sectional study in North Indian population - Singhal, Gaurav; Bhardwaj, Shilpa; Ahirwar, Ashok Kumar; Sharma, Harish C. (International Journal of Research in Medical Sciences, 2020)
Background: Cardiovascular disease (CVD) is the most common cause of death worldwide. The present study was conducted to study uric acid as a potential biomarker in predicting the severity of CVD in terms of vessel involvement. Methods: A cross-sectional study, conducted at Rajiv Gandhi Super Speciality Hospital, Tahirpur, Delhi. A total of 52 consecutive male and female patients age between 30 to 70 years was included in this study. Written informed consent was obtained from all the enrolled patients. Automated analysers were used for the analysis of blood glucose, lipid profile and serum uric acid level. IBM SPSS Statistics (Version 20.0, IBM SPSS, IL, USA) was used for the statistical analyses. Results: In this study, a total of 52 consecutive patients were divided into three groups; single-vessel disease (n=19), double vessel disease (n=19) and triple vessel disease (n=14). Biochemical profile of all the groups was calculated. A group of triple vessel disease patients showing higher amount (164±42 mg/dl) of cholesterol level as compared to the other two groups (157±34 mg/dl). The mean level of serum uric acid levels significantly differed and its mean levels increases as the severity of vessel diseases increases. The receiver operating characteristic curve shows the uric level has 71% sensitivity and 52.5% specificity for detecting the severity of coronary vessel disease. Conclusions: This study demonstrated an increased serum uric acid levels were associated with increased severity of vessel disease, and serum uric acid is an independent risk factor for coronary artery disease.